2006
DOI: 10.2337/diabetes.55.03.06.db05-0015
|View full text |Cite
|
Sign up to set email alerts
|

Tomosyn Is Expressed in β-Cells and Negatively Regulates Insulin Exocytosis

Abstract: E xocytosis is delicately regulated via dynamic protein-protein interactions between different protein components localized to the plasma membrane, the secretory vesicle membrane, and the cytoplasm. According to the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) hypothesis (1,2), the vesicular-SNARE vesicleassociated membrane protein (also called synaptobrevin) interacts with the cognate target-SNAREs syntaxin and synaptosomal-associated protein of 25 kDa (SNAP-25) to form a core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 36 publications
6
58
0
Order By: Relevance
“…Moreover, the study by Tomas and colleagues localized the defect to aberrant insulin-granule docking at the plasma membranespecifically, loss of coupling between granules and plasmamembrane syntaxin 1A, which, the authors show, occurs through a novel interaction with the granule protein granuphilin (Tomas et al, 2008). Syntaxin 1A can also associate with the exocytosisinhibiting protein tomosyn and the Munc accessory factor double C2-like domain-containing protein β (Doc2β), although the function of these interactions in biphasic insulin release is untested (Cheviet Zhang et al, 2006). Because Munc18a associates with the syntaxin-1A isoform, which is required for first-phase secretion only, it is hypothesized that Munc18a will also be required specifically for this phase, although this remains to be tested in islets.…”
Section: Munc18amentioning
confidence: 99%
“…Moreover, the study by Tomas and colleagues localized the defect to aberrant insulin-granule docking at the plasma membranespecifically, loss of coupling between granules and plasmamembrane syntaxin 1A, which, the authors show, occurs through a novel interaction with the granule protein granuphilin (Tomas et al, 2008). Syntaxin 1A can also associate with the exocytosisinhibiting protein tomosyn and the Munc accessory factor double C2-like domain-containing protein β (Doc2β), although the function of these interactions in biphasic insulin release is untested (Cheviet Zhang et al, 2006). Because Munc18a associates with the syntaxin-1A isoform, which is required for first-phase secretion only, it is hypothesized that Munc18a will also be required specifically for this phase, although this remains to be tested in islets.…”
Section: Munc18amentioning
confidence: 99%
“…SDF-1, PF4, and angiopoietin 1 were excluded from analysis due to saturation of their respective spots on the array membranes. jci.org Volume 124 Number 10 October 2014 specific for the b-STXBP5 (5′-CTCCGACTTCCGGTTCTTCCTC-3′ and 5′-TTCAGCGTGATGACAAAGGC-3′), m-STXBP5 (5′-CTCCG-ACTTCCGCAAAGATGTC-3′ and 5′-TTCAGCGTGATGACAAAG-GC-3′), and s-STXBP5 (5′-CTCCGACTTCCGATGTGAAAG-3′ and 5′-TTCAGCGTGATGACAAAGGC-3′) isoforms (29,40).…”
Section: At This Stage It Is Unclear Why Stxbp5 Is Important For Secmentioning
confidence: 99%
“…A specific immunoreactive band was only seen in samples bound to the t-SNARE heterodimers, not in those bound to Munc18a-or Munc18c-containing complexes ( Figure 1B). To determine which STXBP5 isoforms were present in human platelets, RT-PCR analysis was performed using random hexamers and oligo d(T) to prime the reverse transcription step, then using isoform-specific primers for PCR (29,40). Only primers for m-STXBP5 produced a product ( Figure 1C), which suggests that m-STXBP5 is the most abundant isoform in platelets.…”
Section: Introductionmentioning
confidence: 99%
“…In neurons and pancreatic β cells, STXBP5 inhibits neurotransmitter release and insulin secretion, respectively (14,15). Zhu and colleagues demonstrated that STXBP5 also inhibits exocytosis in endothelial cells (8).…”
Section: Stxbp5 Inhibits Exocytosis In Endothelial Cellsmentioning
confidence: 99%